In vitro expression of cauliflower mosaic virus genes - Gordon, K. (1988)
The eight major open reading frames (ORFs) of cauliflower mosaic virus (CaMV) have been cloned for in vitro transcription and translation. All the ORFs could be translated. Using antisera against either purified virus or specific gene products, the translation products were screened by immunoprecipitation. The products of ORFs III, IV and V were confirmed as components of the virions. Molecular weights of primary translation products were determined and compared with those found in vivo. A further series of constructs was designed to test whether translation of adjacent ORFs is coupled in a relay-race fashion as proposed on the basis of earlier in vivo mutagenesis studies. Downstream genes on dicistronic RNAs could be translated, although inefficiently. In view of the similarity between the arrangement of the CaMV coat protein and reverse transcriptase genes and the corresponding genes of retroviruses, we asked whether the CaMV reverse transcriptase could be expressed in vitro as a fusion protein, e.g. by ribosomal frame shifting. No such fusion was observed, suggesting that the polymerase gene is translated from its own ATG.